Grand sonata for the piano forte, : Part [2] op. 106 / composed by Louis van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (London; United Kingdom; Cramer, Beale & Co., 2022)
Edition of the Piano Sonata no. 29 in B-flat major, op. 106, the second part (movements 3-4 only), published as "No. 31" in the series "Beethoven's Works edited by J. Moscheles, complete edition" by Cramer, Beale & Co. (201 Regent Street & 67 Conduit Street) in London (and 167 North Street in Brighton) between 1854-1861; reprint of the edition published by Cramer, Addison, & Beale ca. 1834-1839. At foot of title page: "NB In this edition, the utmost care has been taken to mark by Maelzel's metronome the author's time of each movement."